Carbon‐based nonprecious metal electrocatalysts derived from MOFs for oxygen‐reduction reaction. (16th May 2021) - Jafari, Maryam; Parnian, Mohammad Javad; Gharibi, Hussein; Liang, Zibin; Zou, Ruqiang
Summary: Oxygen‐reduction reaction (ORR) is the most critical factor in energy conversion technologies such as fuel cells. Barriers such as the high cost of Pt and its scarce reservoirs worldwide limit the use of the most advanced Pt‐based catalysts for the ORR reaction. Metal–organic frameworks (MOFs) have attracted considerable attention for the production of carbon‐based nonprecious metal electrocatalysts (NPMC) due to their cost‐effective properties and adjustment of MOF as precursors. The new insight of this review article is focused on clarification of synthesis‐structure‐activity correlations of the presented ORR electrocatalysts for fuel cell applications. Classification of different MOF precursors and their final desirable electrocatalysts after the pyrolysis process are discussed. ORR performance (activity and stability) and their fuel cell performances are investigated for different MOF‐derived materials like monometallic, bimetallic composites, and even single‐atom electrocatalysts. Eventually, readers find a deeper understanding and inspiration of the emerging field of nonprecious MOF‐derived catalysts. Abstract : Carbon‐based non‐precious metal catalysts (NPMCs) derived from MOFs are studied. N‐doped porous structures as metal‐free N–C and transition metal‐doped M–N–C are investigated. Correlations among synthesis, structure, and ORR performance are reviewed.